Macrophage VLDLR mediates obesity-induced insulin resistance with adipose tissue inflammation - Kyung Cheul Shin (Nature Portfolio, 2017)
VLDLR regulates cellular lipoprotein uptake and storage. Here, the authors show that VLDLR, expressed on adipose tissue macrophages, is upregulated in obesity and promotes adipose tissue inflammation by upregulating ceramide production and facilitating M1-like macrophage polarization.